2010
DOI: 10.1371/journal.pone.0012563
|View full text |Cite
|
Sign up to set email alerts
|

Lovastatin Inhibits VEGFR and AKT Activation: Synergistic Cytotoxicity in Combination with VEGFR Inhibitors

Abstract: BackgroundIn a recent study, we demonstrated the ability of lovastatin, a potent inhibitor of mevalonate synthesis, to inhibit the function of the epidermal growth factor receptor (EGFR). Lovastatin attenuated ligand-induced receptor activation and downstream signaling through the PI3K/AKT pathway. Combining lovastatin with gefitinib, a potent EGFR inhibitor, induced synergistic cytotoxicity in a variety of tumor derived cell lines. The vascular endothelial growth factor receptor (VEGFR) and EGFR share similar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 39 publications
(79 reference statements)
2
24
0
1
Order By: Relevance
“…Zhao et al demonstrated a novel mechanism in which lovastatin inhibits both ligand-induced VEGFR-2 activation through inhibition of receptor internalization and VEGF activation of PI3K/AKT pathway in endothelial cells [72]. Since angiogenesis has a central role in clinically aggressive hematologic malignancies such as nonHodgkin lymphomas [73][74][75], angioimmunoblastic T-cell lymphoma [76,77], ALL [78], AML [79], and multiple myeloma [80], inhibition of the VEGF-mediated intracellular signal via bevacizumab could be further facilitated by blocking the mevalonate pathway.…”
Section: Inhibition Of Angiogenesismentioning
confidence: 99%
“…Zhao et al demonstrated a novel mechanism in which lovastatin inhibits both ligand-induced VEGFR-2 activation through inhibition of receptor internalization and VEGF activation of PI3K/AKT pathway in endothelial cells [72]. Since angiogenesis has a central role in clinically aggressive hematologic malignancies such as nonHodgkin lymphomas [73][74][75], angioimmunoblastic T-cell lymphoma [76,77], ALL [78], AML [79], and multiple myeloma [80], inhibition of the VEGF-mediated intracellular signal via bevacizumab could be further facilitated by blocking the mevalonate pathway.…”
Section: Inhibition Of Angiogenesismentioning
confidence: 99%
“…We then demonstrated the potential of lovastatin to induce synergistic cytotoxicity in combination with EGFR-TKIs (29). The mechanism of action revolves around the ability of lovastatin to target the activity of EGFR and other RTKs enhancing the cytotoxicity of EGFR-TKIs in HNSCC cells (30,31). These studies eventually led to a phase I clinical trial of rosuvastatin and erlotinib at our Institute that showed disease stabilization, although the high dose of statins used had undesirable muscle pathologies in a significant number of patients (ClinicalTrials.gov Identifier: NCT00966472), suggesting an alternative approach to improve cancer targeting while minimizing the side effects of the treatment regimen.…”
Section: Introductionmentioning
confidence: 99%
“…To this end, drugs which show higher cytotoxicity at low pH, including statins and cantharidins would be conventional candidates for co-treatment of mesothelioma. In fact, the combination treatment of solid tumors with statins enhanced anti-tumor drugs in vivo (Agarwal et al, 1999;Gao et al, 2010;O'Brien et al 2003;Zhao et al, 2010). So the development of new compounds with anti-tumor activity preferentially at low pH would be useful for chemotherapy of mesothelioma.…”
Section: Resultsmentioning
confidence: 99%